Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1038/sj.sc.3100725
|View full text |Cite
|
Sign up to set email alerts
|

Intraurethral stent prosthesis in spinal cord injured patients with sphincter dyssynergia

Abstract: This study is an analysis of the Memotherm 1 prosthesis in spinal cord injured patients with Detrusor-external sphincter dyssynergia (DESD). Twenty-four patients were evaluated urodynamically before and after placement of the intraurethral stent prosthesis. All the patients had been chronically managed with an indwelling urinary catheter, intermittent catheterization or condom catheters. Sixty-six per cent had history of recurrent urinary tract infection, 37% had symptoms of autonomic dysre¯exia. Nine patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…Garcia et al 47 reported on the use of the Memotherm stent in 24 spinal cord injured men with DSD. Nine had undergone previous sphincterotomy.…”
Section: Balloon Dilatation and Stentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Garcia et al 47 reported on the use of the Memotherm stent in 24 spinal cord injured men with DSD. Nine had undergone previous sphincterotomy.…”
Section: Balloon Dilatation and Stentsmentioning
confidence: 99%
“…In the 18 with correct stent placement mean LPP decreased from 90 to 35 cm H 2 O. 47 Sauerwein et al 48 used the UroLume Wallstent in 51 patients with SCI and DSD. The patients were followed for between 12 ± 36 months.…”
Section: Balloon Dilatation and Stentsmentioning
confidence: 99%
“…Percentages vary a lot between series, varying between 7.7 and 71.4%. 10,11,19,22,25,28 There is an increase in this complication as the follow-up period is extended.…”
Section: Discussionmentioning
confidence: 99%
“…Our experience in this field of studying 24 patients for an average time of 15.4 months has already been reported. 19 We now present a higher number of patients and a long-term follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Several different urethral stent designs have been tested in various trials including the UroLume ® (American Medical Systems, Minnetonka, MN, USA) (Chancellor et al, 1999b), Memokath ® (Doctors & Engineers A/S Ltd., Kvistgaard, Denmark) (Low and McRae, 1998;Hamid et al, 2003), Memotherm ® (Bard Corp., Covington, GA, USA) (Juan Garcia et al, 1999) and Ultraflex ® (Boston Scientific Corp., Natick, MA, USA) (Chartier-Kastler et al, 2000). The UroLume, Memotherm and Ultraflex are flexible wire mesh tubes while the Memokath is a helically wound wire.…”
Section: Urethral Stentsmentioning
confidence: 99%